(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2024)
This research aims to analyze the forms and models of violence that have occurred recently, so that personal or community groups can avoid violence. Violence that has occurred recently is not only personal, but also mass and even more so violence occurs globally. The general assumption that "the more modern humans are, the more cultured they will be" is not proven. The violence that occurs now at the community level is actually driven by modern humans or at least those who live in modern times. The issue of violence has become a kind of culture in the mind of modern society today. Tragically, violence is used as the only tool to solve various problems that arise due to various differences that are not substantial.